Development and psychometric evaluation of E-Learning Assessment Scale in Higher Education - Sevil Çiçek Özdemir; Ayten Şentürk Erenel; Şengül Yaman Sözbir; Sıdıka Pelit Aksu; Canan Uçakcı Asalıoğlu (Sakarya Üniversitesi Eğitim Fakültesi Dergisi)
E-learning is a fairly recent and fleetly expanding trend of education that increased particularly during the COVID-19 epidemic. thus, assessing thee-learning with standardized tools has gained significance. This study aims to develop an e-learning assessment scale for university students. This methodological study was performed with 434 students in Türkiye. The item pool of the scale was created grounded on the applicable literature. The data were estimated using descriptive statistics, explanatory and confirmational factor analysis (CFA), Pearson correlation analysis, t-test for dependent variables and Cronbach alpha coefficient. The content validity index of this scale calculated according to experts‟ opinions ranged from 0.84-1.00. According to the explanatory factor analysis, two factors had an eigenvalue> 1. These two factors reckoned for 68.6 of the total variance. CFA showed favourable results for Chi forecourt/ degrees of freedom (χ2/df), comparative fit indicator (CFI) and root mean square error of approximation (RMSEA). The Cronbach alpha of the scale was 0.96. The Cronbach alpha measure of the sub-dimensions independently,0.94 and 0.93. The E-Learning Assessment Scale had strong test-retest reliability. In conclusion, the 18-item E-Learning Assessment Scale was a valid and reliable tool for assessing e-learning. The scale enables students to assess the e-learning process.